Increase In Macro Nutrients By Adding Banana Waste To Liquid Organic Fertilizer - Hendrawani, Hendrawani; Hatimah, Husnul; Hulyadi, Hulyadi (Jurnal Ilmiah Mandala Education (JIME), 2021)
Liquid organic fertilizer is a solution from the fermentation of organic materials by involving microorganisms as a destructor of macromolecular compounds into minerals that are easily absorbed by plants. The quality of organic fertilizers is the main ingredient to get productive plants. The quality of organic fertilizer is determined by the concentration of macro nutrients such as nitrogen (N), potassium (K), and phosphorus. Getting high amounts of macronutrients fertilized organically is not easy. Macro-nutrients in organic waste with high concentrations are very difficult to obtain because each organic waste does not have all three macro-nutrients simultaneously. It takes a combination of organic waste to increase the concentration of macro nutrients in organic fertilizers. The combination of tofu whey with banana waste is one technique to obtain organic fertilizers that are high in phosphorus content. This study aims to obtain the effect and conditions of fermentation on the addition of mass of banana waste to produce optimum levels of phosphorus (P) in liquid fertilizer of tofu waste. The type of research used is pre-experimental research. The design of this study used a completely randomized design (CRD) with two factors, namely the first factor was the mass of banana waste (X) (X1 = 250 grams, X2 = 500 grams, X3 = 750 grams) and the second factor was the fermentation time (Y) (Y1 = 14 days, Y2 = 28 days, Y3 = 42 days). Determination of phosphorus content using UV-Vis spectroscopy instrument. Parameters measured were phosphorus (P) levels in liquid organic fertilizer. The independent variables in this study were the mass of banana waste and fermentation time, while the dependent variable in this study was the phosphorus content of the liquid fertilizer produced. The results of the analysis show that the phosphorus content (P) produced is X1Y1 = 0.1%, X2Y1 = 0.5%, X3Y1 = 0.09%, X1Y2 = 0.5%, X2Y2 = 2%, X3Y2 = 1.9 %, X1Y3 = 0.2%, X2Y3 = 0.5% and X3Y3 = 0.5%. There is an effect with the addition of a mass of banana waste as much as 250 grams at a 12-day fermentation time. It can be concluded that the liquid fertilizer produced has exceeded the SNI quality standard.